Forced carbonation of recycled concrete aggregates - Marc-Patrick Pfleger; Markus Vill (Acta Polytechnica CTU Proceedings, 2022)
The production of concrete, especially the contained cement clinker, causes a high proportion of the manmade gaseous air pollution. Studies show that the decarbonation of limestone effects roughly 8% of worldwide CO2 emissions, which underlines the need for action and research. Due to the present building and infrastructure stocks and their obsolescence, or rather replacement, the amount of demolition material is permanently increasing. In many cases the demolition material consists of high-quality concrete, which could be used again as recycled aggregate in the production process to conserve sources of raw materials. Most of the concrete waste is not carbonated which means that the potential as CO2 sink can be exploited in the course of the recycling process. Since the recycled and carbonated material is used as a replacement for primary raw material, the state of carbonation itself is irrelevant to any steel corrosion or associated problems. The main objective of this work was to investigate the CO2 absorption of concrete waste, to investigate and prove its use as a possible carbon sink. At this point, the carbonation velocity had to be optimised by the use of special equipment. First test series show that the ecological footprint of concrete can be significantly reduced if concrete waste is used for carbon storage and admixed as recycled aggregate during the production process. The aim of this study was to point out further possibilities for the ecological optimisation of concrete besides alternative binders, which are the subject of research in various projects worldwide.